A canoagem como espaço não formal em educação matemática - Haetinger, Márcio Ricardo da Silva (2017)
This paper is a result of a master’s degree research that had as main objective to show that sports activities of canoeing, developed in a non-formal space of Education, can help in the understanding of mathematical concepts worked at school. The research was developed with a group of young canoeists, participants in a social project and who practice canoeing as a sport activity along the banks of Jacuí River in Cachoeira do Sul/RS. As a theoretical reference it was sought a support from authors who talk about the importance of using non-formal spaces of Education. This is a qualitative approach research that presents as methodology the field research of ethnographic type, having initially as instruments for the data collect the application of a questionnaire to the students/athletes, the realization of observations at the group space and also the research’s actors narratives. From this, some pedagogical nature interventions were made aiming to approach some mathematical concepts inherent to canoeing actions lived in the group and by the group of young people participant in the project, in order to ally canoeing practice and Mathematical Education. As an investigative matter, we have: does the sports activities of canoeing practice of a young people group, participant in a social project, can assist in the understanding of mathematical concepts? For the data analysis we recurred to the discourse analysis, considering that it was sought to return the attention to details of possible perceptions in the discourses from the actors, subjects of the research. From the analyzed data we have indications to affirm that it is possible to realize the importance of Mathematical Education in non-formal spaces of Education and, in this specific case, the contribution of canoeing practice in the learning of mathematical concepts related to the activities of the social project of Cachoeira Association of Canoeing and Ecology.